Out-of-hospital cardiac arrest survivors sent for emergency angiography: a clinical score for predicting acute myocardial infarction. Issue 2 (1st March 2017) - Zeyons, Floriane; Jesel, Laurence; Morel, Olivier; Kremer, Hélène; Messas, Nathan; Hess, Sebastien; Crimizade, Ulun; Reydel, Philippe; Tritsch, Laurent; Ohlmann, Patrick
Abstract: Background: Out-of-hospital cardiac arrest (OHCA) remains a major public health issue. Emergency coronary angiography and percutaneous coronary intervention might improve survival, especially when cardiac arrest is caused by acute myocardial infarction (AMI). However, identifying patients with AMI after OHCA remains challenging. The aim of this study was to determine the clinical and ECG criteria in OHCA that may help to identify better the patients with AMI. Methods: Consecutive OHCA patients who underwent emergency coronary angiography in our centre between 2009 and 2013 were included in this retrospective single-centre observational study. Results: A total of 177 patients with complete datasets were included. Significant coronary artery disease was found in 71% of the patients, and 43% presented with AMI. The independent predictors of AMI were ST elevation in any lead including aVR (odds ratio (OR) 18.06; 95% confidence interval (CI) 6.6–49.38), chest pain before cardiac arrest (OR 4.05; 95% CI 1.55–10.54) and an initial shockable rhythm (OR 2.99; 95% CI 1.34–6.45). An additive score that included these three predictors yielded a sensitivity and a specificity for detecting AMI of 93% and 63%, respectively. Conclusions: These data suggest that fewer than half of patients with OHCA undergoing emergency coronary angiography present with AMI. The identification of OHCA patients with AMI might be improved by a simple score using post-resuscitation ECG and simple clinical criteria.